Quantitative study on image reconstruction in frequency domain diffuse optical tomography - Chin, Hooi Ling. (2011)
Diffuse Optical Tomography (DOT) is a non-invasive imaging modality which depends on modeling the propagation of near-infrared light in tissue to determine optical properties such as absorption and scattering coefficient of the medium. This technique has a number of clinical applications, especially in medical imaging where it could help resolve oxygen saturation and total hemoglobin concentration (THC) in tissue and potentially be used in imaging malignant tumors. In this project, a main simulation and reconstruction tool, Near Infrared Frequency domain Absorption and Scatter Tomography (NIRFAST), is used for image reconstruction. NIRFAST is an FEM based package for modeling near-infrared light transport in tissue. A major challenge was to work out how to interface experimental data with the tools provided by the package. A deep understanding of the inner algorithms of the package is needed in order to process the data into an acceptable form, and it is often down to basic trial and error tactics to find the best parameters to use in various methods. Therefore, this report will focus on how different methods and parameters in the software affect the reconstruction results and the detailed mathematical operations required for integration of experimental data into NIRFAST. The reported inhomogeneity findings demonstrated favorably that NIRFAST is a suitable tool for FD DOT image reconstruction.